Masculinities in a global era - Gelfer, Joseph (International and Cultural Psychology, 2014)
The ongoing movement toward globalization challenges us to reconsider issues of individual identity. Are we evolving into citizens of the world? How crucial is nationality? And for men, what does it now mean to be male? Diverse answers to this provocative question are analyzed in Masculinities in a Global Era in its theoretical models, study findings, and compelling examples. Multiple dynamics are displayed in these chapters--gender and sexuality, tradition and change, local and global, East and West--as male identity is defined as a work in progress in locations as disparate as Ireland and Indonesia. Contributors analyze the larger paradoxes and ambiguities of studying masculinity and globalization, and of the gender contexts of globalization as a social phenomenon. As a volume, the perspective is multinational, multiracial, sexually inclusive, and optimistic about globalization as a positive transformative force. Among the featured topics:  Examining individual differences in masculine honor beliefs. Bengali men and the transnational middle class in India. Fluid masculinities: the case of Bahrain. Gendered cultured citizenship in male emancipation projects in the Netherlands. Hypospadias, the "Bathroom Panopticon." Transgender identity and acceptance: the Muxes of Juchitan, Mexico.  Crossing myriad domains much like globalization itself, Masculinities in a Global Era is a thoughtful reference for researchers in a variety of disciplines, including cross-cultural studies, gender studies, sexuality, sociology, and developmental and cross-cultural psychology.